2009
DOI: 10.12702/1984-7033.v09n03a03
|View full text |Cite
|
Sign up to set email alerts
|

Yield stability and adaptability of maize hybrids based on GGE biplot analysis characteristics

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 19 publications
1
33
1
7
Order By: Relevance
“…Moreover, by means of this method, it was apparently established that high and stable yields could be attained only in specific environment. Other researchers observed that GGE biplot analysis is a suitable device for detecting experimental environments to select best genotypes in field crops as well (Balestre et al, 2009;Ilker et al, 2009;Oliveira et al, 2010;Tonk et al, 2011;Khalil et al, 2011;Beyene et al, 2011, Nzuve et al, 2013Mortazavian et al, 2014;Miah et al, 2015).…”
Section: Relationship Among the Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, by means of this method, it was apparently established that high and stable yields could be attained only in specific environment. Other researchers observed that GGE biplot analysis is a suitable device for detecting experimental environments to select best genotypes in field crops as well (Balestre et al, 2009;Ilker et al, 2009;Oliveira et al, 2010;Tonk et al, 2011;Khalil et al, 2011;Beyene et al, 2011, Nzuve et al, 2013Mortazavian et al, 2014;Miah et al, 2015).…”
Section: Relationship Among the Environmentsmentioning
confidence: 99%
“…Genotype × environment interaction (GE) have shown there supremeness for delineating stability of genotypes and have partitioned variation that better aid for selection of consistent stable genotypes in many different studies (Dehghani et al, 2006;Yan et al, 2007;Sabaghnia & Sabaghpour, 2008). There are several methods for stability analysis among which GGE biplot analysis was used in the present study to deduce stability of the crop with aim to investigate the stability of seed yield in amaranths and graphically summarize and considerate the assets of G and GE interaction (Yan & Kang, 2003;Samonte et al, 2005;Dehghani et al, 2009, Balestre et al, 2009Oliveira et al, 2010;Tonk et al, 2011). Present study was undertaken for the first time to gather information about GE interaction of different amaranth genotypes for high seed yield using three year data using GGE biplot analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, Balestre et al (2009) comparando os métodos GGE Biplot e AMMI afirmam que o modelo GGE Biplot é superior ao AMMI apenas quando há a seleção do AMMI1, neste caso há superioridade da GGE Biplot devido à maior captação da soma de quadrados e acurácia preditiva, enquanto o AMMI2 foi superior. Segundo Carbonell et al (2007), o método REML/ BLUP é superior à análise AMMI, pois os efeitos gené-ticos e da interação são tratados como fixos em AMMI, atuando apenas em nível fenotípico, enquanto REML/ BLUP atua em nível genotípico.…”
Section: Introductionunclassified
“…Besides, although the GGE M Balestre et al biplot analysis is very similar to AMMI 1, it usually explains a greater proportion of G + GE and could, in most cases, result in a more accurate graphic (Yan et al 2007, Gauch et al 2008, Balestre et al 2009a). This statement can however not be taken as a rule (Balestre et al 2009b).…”
Section: Introductionmentioning
confidence: 99%